The phenomenological self: owner and agent, through thick and thin - Lenzo, Edward Anthony, author; MacKenzie, Matthew, advisor; McShane, Katie, committee member; Davalos, Deana, committee member (Colorado State University. Libraries, 2014)
The central work of this thesis is to compare and contrast two phenomenological notions of self: the minimal self, a Husserlian notion articulated by Dan Zahavi, and SESMET, as developed by Galen Strawson. The minimal self conception takes the self to be a kind of diachronically unified owner of experience and agent of action, but takes unification and ownership to entail more than may be justified. Strawson neglects to construe diachronicity appropriately, misconstruing the phenomenological nature of the stream and rejecting agency in toto, but covertly reintroduces agency in a metaphysical guise. Neither conception is an appropriate notion of self, but I propose a "hybrid" account that incorporates appropriately nuanced views of persistence and agency. I conclude by suggesting potential problems for this view, while highlighting its applications. In Chapter 1 I explicate and critique Strawson's SESMET, detailing its insights into the investigation of self and developing concerns with the account. In Chapter 2 I analyze Edmund Husserl's account of internal time-consciousness, which serves as the foundation of Zahavi's minimal self. In Chapter 3 I link this Husserlian framework to the basic sense of self (the feeling of being a self), proceeding by philosophical and psychopathological considerations, clearly define the minimal self, compare it to SESMET, and argue that these notions are prima facie equally legitimate. In Chapter 4 I contrast these notions, focusing on issues raised throughout and the resolutions available for each "self". I reject both notions, but use their respective strengths and weaknesses to propose a promising hybrid view. I then suggest possible faults of this view.
Keywords: Husserl; metaphysics; phenomenology; philosophy of mind; philosophy of psychopathology; self